RETRACTED: Innovative analysis in climate change: Evidence from developed European countries - Barykin, Sergey; Yadykin, Vladimir; Badenko, Vladimir; Sergeev, Sergey; Bezborodov, Andrey; Lavskaya, Kristina; Poza, Elena de la; Morkovkin, Dmitry; Shchukina, Tatyana; Veynberg, Roman; Rassylnikov, Igor; Svechnikova, Vera; et al. (Frontiers in Environmental Science, 2022)
Since the turn of the twentieth century, the whole world has entered a period of technological singularity. It is also predicted that the pace of innovation in climate change, generational change of technologies will constantly increase. This work aims on the economicall and social strategy for bringing an innovative product to the market is set. The methodology is based on a dynamic assessment of the development of consumer demand in the context of innovative proposals. In the article, the results are obtained and the volume of investments in the development and development of innovations is determined, which will optimize the balance between curtailing the volume of output using the previous technology in climate change and increasing the production and sale of an innovative product in climate change. The main result is the total profit from the demand in the consumer market for products based on the old and new technologies in climate change, since the old and new business processes entail significant financial costs.